2022
DOI: 10.1101/2022.08.15.504039
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic silencing of AKT induces melanoma cell death

Abstract: Aberrant activation of the PI3K-AKT pathway is common in melanoma but efforts to drug this pathway have proven largely ineffective in patients. In this study, we observed that pharmacological inhibition of AKT was ineffective whereas genetic silencing of all three AKT paralogs significantly abrogated melanoma cell growth through effects on mTORC signaling. This phenotype could be rescued by overexpression of AKT but was dependent on kinase activity. Interestingly, expression of the serine/threonine kinase SGK1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 45 publications
0
3
0
1
Order By: Relevance
“…Moreover, activated AKT was sufficient to rescue the suppression of PTENdeficient melanoma by acute PTEN restoration. In a complementary study, Parkman et al demonstrate that genetic silencing of all three AKT paralogs diminishes the proliferation and induces death of PTEN-deficient melanoma cells (Parkman et al, 2022). These findings support the notion that AKT is the predominant effector downstream of PIP3, promoting melanomagenesis upon the loss of the PTEN lipid phosphatase activity.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Moreover, activated AKT was sufficient to rescue the suppression of PTENdeficient melanoma by acute PTEN restoration. In a complementary study, Parkman et al demonstrate that genetic silencing of all three AKT paralogs diminishes the proliferation and induces death of PTEN-deficient melanoma cells (Parkman et al, 2022). These findings support the notion that AKT is the predominant effector downstream of PIP3, promoting melanomagenesis upon the loss of the PTEN lipid phosphatase activity.…”
Section: Discussionmentioning
confidence: 79%
“…One such parallel pathway could be the SGK pathway, which has previously been implicated in melanoma (Scortegagna et al, 2015). Indeed, Parkman et al identified a compensatory increase in SGK1 expression upon pan-AKT silencing and demonstrate superior melanoma cell killing by combined AKT and SGK inhibition (Parkman et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Tumor growth and development are encouraged by the PI3K/Akt pathway, which is abnormally active in malignancies and crucial for many cellular processes. By examining the upstream and downstream nodes of this pathway (Supplementary Figure S4), it may be feasible to fully comprehend its function [44]. Furthermore, the emergence of treatment resistance occurs along with this pathway activation [45].…”
Section: Drugs That Attack Cells With Altered Braf Genementioning
confidence: 99%
“…Ainda referente a proliferação e sobrevivência, os genes de resposta a mitógenos CCL2 e SGK1 são alvos regulados por RMEL3, e estes genes já foram relacionados com maior resistência adaptativa à inibidores de BRAF e a proliferação de melanomas BRAF V600E (Parkman et al, 2022;Vergani et al, 2016), reforçando mais uma vez a associação de RMEL3 com BRAF V600E (Goedert et al, 2016) Dados anteriores do grupo já indicavam que a expressão de RMEL3 associado à supressão da apoptose (Goedert et al, 2016;Cardoso et al, 2019). Nesse trabalho vimos que a ausência de RMEL3 aumentou a apoptose celular nas células A375 tanto na presença de mitógenos (Figura 24) quanto na ausência (Figura 25).…”
Section: Discussionunclassified